OPTIMIZATION OF DELAY AT INTERSECTION IN ANTICIPATE STUCK ON THE TRAFFIC BY USING SOFTWARE SIDRA INTERSECTION 8.0 (CASE STUDY : SIMPANG BPKP BANDA ACEH) - Malia, Rezqi; Dinda, Raina Parmitalia; Alvisyahri, Alvisyahri; Chaira, Chaira (Journal of Civil Engineering, 2023)
Simpang BPKP Banda Aceh is one of the signalized intersection with four approaches. so there are 16 crossing, 8 diverging, and 8 merging, between vehicles such as delay and congestion. This research aims to analysis the intersection in existing condition and redesign condition by using SIDRA Intersection 8.0 as a software. Software SIDRA Intersection 8.0 (analytical model) is a fixed minimum capacity for each minor movement is set by the user. The data was collected from institute from a video by using cctv at research area. The data from a video was include volume of vehicle, distances (upstrem, downstream, and negotiation) and travel time. In existing condition. Total demand flow is 1060 pcu/h. Approach delay 96,8 sec and level of service is F. The geometry for redesign condition is designing roundabout at that intersection. This assumption is made in the condition an unsignalized intersection.  Total demand flow in redesign condition at Simpang BPKP Banda Aceh is 1060 pcu/h. Approach delay 3,8 sec and level of service is A.